She's all that [videorecording (DVD)] - Iscove, Robert; Prinze, Freddie, Jr; Cook, Rachael Leigh, 1979-; Lillard, Matthew, 1970- (Paramount, 2020)
When he's dumped by his beautiful girlfriend, Zack Siler bets a classmate that he can turn any girl in school into the prom queen.